2009
DOI: 10.1089/fpd.2008.0213
|View full text |Cite
|
Sign up to set email alerts
|

Emergence, Distribution, and Molecular and Phenotypic Characteristics ofSalmonella entericaSerotype 4,5,12:i:–

Abstract: Salmonella spp. represent one of the most common causes of bacterial foodborne illnesses around the world. The species Salmonella enterica contains more than 2500 serotypes, and emergence of new human pathogenic Salmonella strains and serotypes represents a major public health issue. Salmonella enterica subsp. enterica serotype 4,5,12:i:- represents a monophasic variant of Salmonella Typhimurium, which has rarely been identified before the mid-1990 s. The prevalence of this serotype among human salmonellosis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
110
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(121 citation statements)
references
References 36 publications
4
110
0
7
Order By: Relevance
“…In this study, we found only 1 monophasic variant of S. Typhimurium (STM032/04) from a hospitalized patient in 2004. It has been known that the majority of Salmonella 4, [5],12:i:-strains reported in European and Asian countries showed MDR phenotypes (8). We found that the monophasic STM032/04 strain in this study was resistant to AMP, GEN, and TET, in addition to NAL; this finding was similar to those obtained for monophasic strains in Thailand (37).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In this study, we found only 1 monophasic variant of S. Typhimurium (STM032/04) from a hospitalized patient in 2004. It has been known that the majority of Salmonella 4, [5],12:i:-strains reported in European and Asian countries showed MDR phenotypes (8). We found that the monophasic STM032/04 strain in this study was resistant to AMP, GEN, and TET, in addition to NAL; this finding was similar to those obtained for monophasic strains in Thailand (37).…”
Section: Discussionsupporting
confidence: 88%
“…The worldwide emergence and spreading of monophasic Salmonella 4, [5],12:i:-has been reported since 1990s (8). In Asia, the isolation of this clinically important NTS from clinical samples has been reported in Thailand and Taiwan (35,36) but not in Malaysia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salmonella enterica subspecies (subsp) enterica serovar 4, [5],12:i:-has been frequently isolated from humans and other animals worldwide (reviewed by Moreno-Switt et al, 2009). Considered an emergent and multi-drug resistant serovar, S. enterica 4,5,12:i:-has been responsible for outbreaks in several continents (Echeita and Usera, 1998;Amavist et al, 2005;Mossong et al, 2006;Hauser et al, 2010;Hopkins et al, 2010;CDC, 2011;Raguenaud et al, 2012;Guillier et al, 2013;Mandilara et al, 2013;Gallati et al, 2013;Mulvey et al, 2013;Arguello et al, 2014;Garcia et al, 2014).…”
Section: Introductionmentioning
confidence: 99%